Structure of a pleiomeric form of poly d(AT):poly d(AT). - Millane, R P (1984)
A chemically simple polynucleotide duplex, poly d(AT):poly d(AT), has been trapped in a fibrous form with a complex helical secondary structure with a large (7.4 nm) axial repeat 24 nucleotides long. The motif which is repeated by the symmetry elements is a hexanucleotide in which two residues (both TpA) have the less common gauche minus conformation at C3'-O3' and consequently distinctive phosphate orientations. This reinforces earlier conclusions that PypPu nucleotides tend to have different shapes from PupPy nucleotides and that DNA surfaces may signal what base sequences lie beneath them. The morphological differences between this pleiomeric DNA polymer and closely-related, but more symmetrical allomorphs are just as great as those observed in short DNA fragments in crystals.